Pech Piélat (Séniergues, Lot) : un relais routier antique en pays cadurque - Laurent Grimbert; Vivien Mathé; Marion Druez (Gallia)
The Pech Piélat digs (Séniergues, Lot) of Autumn 1998 have revealed the existence of an antique edifice and road that were hitherto unknown. Situated in a proto-historical location from the Iron Age, the edifice dates from the end of the 1st century AD, followed by a phase of renovations, notably the addition of a thermal wing at the beginning of the 2nd century AD. The date at which the site was abandoned is, however, difficult to determine (perhaps the 5th century AD). During the excavation phase, the restricted surface area of the project meant that it was difficult to assess its purpose. In order to resolve a number of questions, a programmed operation of electrical resistivity tomography (ULR Valor and UMR 6250 CNRS, La Rochelle University) was conducted in March 2008 (financed by the DRAC Midi-Pyrénées) on areas that were not accessible during the digs. The principal findings are presented in this study. A comparison of the archaeological data and the results of the tomography has enabled the identification and description of a small relay station along the Divona-Augustoritum route. The presence of the road, a particularly rare example of an antique route clearly identified in the Cadurci region, provides new elements for the mapping of the ancient routes.